INOVASI PENDAMPINGAN FOTOGRAFI PRODUK BERBASIS SMARTPHONE UNTUK TRANSFORMASI VISUAL MARKETING UMKM DI DESA MEKAR JAYA - Jamiati KN; Nida Handayani; Sarrah Kurnia Fadhillah (LP2M Universitas Ibrahimy, 2025)
The transformation toward digital marketing has become a critical challenge for rural micro, small, and medium enterprises (MSMEs) in the era of technological disruption, yet limited knowledge and infrastructure often hinder adaptation. This study aims to identify the effectiveness of product photography mentoring using smartphones as an innovative and affordable solution for developing visual marketing among MSMEs in Mekar Jaya Village. The community service program adopted a Community Development approach and participatory training methods involving 50 local MSME actors. Implementation was conducted in three stages: (1) preparation and needs analysis, (2) intensive training and hands-on practice, and (3) mixed-method evaluation and monitoring. Results indicated a significant improvement in participants’ skills, with a 77% average increase based on pre- and post-test evaluations. Product photo quality improved across lighting (50%), composition (50%), focus (35%), and background (45%). Economically, 40% of participants secured new customers, achieving an average monthly revenue increase of 32% one month post-program. The program’s success validated the Low-Cost High-Impact Visual Marketing model, which leverages community-owned technological resources, offering a cost-effective empowerment strategy compared to expensive equipment investments or professional outsourcing.